Bridging the Theological-Digital Divide: Professional Readiness in Implementing Progressive Authentic Assessment under Kurikulum Merdeka - Zaenal Jaenudin; Maulana Hasanudin; Imam Turmidzi (Journal of Knowledge and Collaboration, 2026)
The implementation of the Merdeka Curriculum and the 2013 Curriculum in Indonesia marks a significant paradigm shift from conventional product-oriented evaluation toward a comprehensive process-oriented assessment system. This study examines the conceptualization and implementation of authentic assessment in Islamic Religious Education (IRE) through the lens of educational progressivism. Employing a qualitative approach through literature research and contextual analysis informed by empirical field insights, the study explores how authentic assessment functions as a progressive instrument for fostering students’ holistic development across the affective, cognitive, and psychomotor domains. The findings indicate that a progressive authentic assessment framework requires a structural balance between theoretical principles and practical real-world application. Within the affective domain, instruments such as anecdotal records, peer feedback, and reflective journals promote multicultural values and public accountability. Cognitive assessment extends beyond mere memorization to encompass constructive and contextualized tasks, while the psychomotor domain utilizes e-portfolios and real-world performance activities. Nevertheless, operational constraints—including technological disparities and teacher readiness—remain major challenges. This study concludes that progressive authentic assessment in Islamic Religious Education serves as an educational reflection tool that bridges theological, sociological, and psychological dimensions, positioning learners as active and autonomous agents.